Broadband scanning leaky‐wave antenna based on interdigital coupled‐type composite right/left‐handed transmission line structure. Issue 12 (8th September 2020) - Li, Tianpeng; Lei, Xue; Gao, Jun; Cheng, Baowei; Xu, Zhijian
Abstract: Owing to its unique nonlinear dispersion characteristics, the composite right/left‐handed (CRLH) transmission line (TL) have been widely implemented in the design of leaky‐wave antennas. A novel CRLH‐TL unit is proposed in this article using the metal patch and pillars to connect the interdigitated line. Not only the parasitic resonance in the conventional interdigital CRLH TL is eliminated by etching the annular gap on the ground, but the miniaturization is also achieved. Then, a broadband high‐performance full‐plane scanning leaky‐wave antenna is designed based on the unit in balanced state. The measured bandwidth with return loss <−10 dB is 3.97 to 5.86 GHz and the peak gain over the operating bandwidth is higher than 9.17 dB. There is no parasitic resonance in the operating bandwidth and the antenna has a lower operating frequency than the classic Interdigital Coupled‐Type (ICT) CRLH leaky‐wave antenna of the same length.